Analisis Aliran Udara Di Sekitar Truk Pikap Yang Dipasangi Terpal Di Bagian Bak Menggunakan Cfd - Bhyantarah Nugraha, Fadhil; Adhi Suryawan, Anak Agung; Ghurri, Ainul (Teknik Desain Mekanika; Vol 11 No 1 (2022): Januari 2022 : Teknik Desain Mekanika, 2022)
Abstract Pickup trucks are one of the most widely used vehicles in Indonesia. Pickup trucks are useful for transporting goods such as food, furniture, cargo, livestock, and also for transporting passengers in areas where public transportation is scarce. Usually, pickup trucks are often fitted with tarpaulins. The tarpaulin installation models that are often used include the flat model or Tonneau Cover, the Aerocap, and the ‘Cincing’ model. This study aims to determine and describe the aerodynamic factors that affect the performance of a pickup truck when a tarpaulin is attached to the cargo bed and how it affect the aerodynamic force of the vehicle using the Computational Fluid Dynamic (CFD) simulation method with ANSYS Fluent. The simulation results show that the tarpaulin model with a broad and box-shaped surface like the Aerocap Tarpaulin Model with an angle of 0o (Type B) produces the largest drag force due to increased skin drag and circulation in the wake which ultimately increases the drag coefficient compared to the baseline model. The tarpaulin model with the lowest drag coefficient is shown by the Aerocap Tarpaulin with an angle of 15.72o (Type C), because the shape has a slope that causes the flow around the pickup to be more aerodynamic and lower. The lift force that occurs is very small with insignificant changes, which is normal for this pickup-shaped object. Keywords: Aerodynamic, Computational Fluid Dynamic (CFD), Drag Force, Coefficient of Drag, Streamline